Expression from the Clostridium perfringens cpe promoter in C. perfringens and Bacillus subtilis. - Melville, S B (1994)
Clostridium perfringens is a source of food poisoning in humans and animals because of production of a potent enterotoxin (CPE). To study the regulation of the cpe gene in C. perfringens, we cloned and sequenced the cpe promoter regions and N-terminal domains from three strains. The cpe promoter region from one strain contained a 45-bp insertion compared with previously published sequences. This insertion was also found in two (of five) other Cpe+ strains. cpe gene expression in C. perfringens was measured by using translational fusions of each promoter type to the Escherichia coli gusA gene, which codes for beta-glucuronidase. For either promoter type, cpe-gusA expression was undetectable throughout exponential growth but increased dramatically at the beginning of the stationary phase. To measure cpe expression in Bacillus subtilis, cpe-gusA fusions were integrated into the B. subtilis chromosome. Both types of promoter exhibited moderate expression during exponential growth; cpe expression increased threefold at the beginning of the stationary phase. Transcriptional start sites were determined by primer extension and in vitro transcription assays. For C. perfringens, both types of promoter gave the same 5' end, 197 bp upstream of the translation start (50 bp downstream of the 45-bp insertion). In B. subtilis, however, the 5' end was internal to the 45-bp insertion, suggesting the use of a different promoter than that utilized by C. perfringens.